Coordination properties of Palladium(II) complex taken as a model of an antitumour agent with some selected amino acids, peptides and DNA constituents (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Pd(DHP)Cl2 complex ( DHP = 1,3-diamino-2-hydroxopropane ), was synthesized and characterized by physico-chemical measurements. The coordination of [Pd(DHP) (H2O)2]2+ with some selected bio-relevant ligands as phenylglycine, phenylalanine, lysine, valine, ethanolamine, glycineamide, glycylphenylalanine, glycylleucine, inosine, guanosine and inosine-5’-monophosphate disodium salt was investigated.Stoichiometry and stability constants of the complexes formed are reported at 25 0C and 0.1M ionic strength. The results show the formation of 1:1 complexes with amino acids. DNA constituents form 1:1 and 1:2 complexes. Peptides form both 1:1 complexes and the coresponding deprotonated amide species. The effect of chloride ion concentration on the formation constant of inosine, taken as a representaive ofDNA constituents, complex with Pd(DHP)2+ was reported.